Ev Evaluative Performance Program E-Tilang di Simpang Raya Kota Surabaya - Wisnu Abdullah Setiadarma; Binti Azizatun Nafi’ah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
ETLE (Electronic Traffic Law Enforcement) is a set of electronic devices that use Automatic License Plate Recognition (ANPR) technology in the form of cameras that automatically detect motorized vehicles and cars with traffic violations E-TLE system, which is part of law enforcement efforts, this system aims to reduce problems caused by traffic violations, such as congestion and accidents, and ensure order on the highway. The e-Tilang system was pioneered by the East Java Regional Police, especially the Surabaya Police, which has this innovation as a crucial role in improving safety and regularity of electronically based traffic, the implementation of ETLE tickets in Surabaya City has increased in 2022 and 2023 compared to 2021. Which in 2021 the ETLE program was intensified due to the Covid-19 pandemic in order to increase the efficiency of technology-based services. The ETLE camera system uses CCTV cameras that are monitored directly by Police Officers with a total of 22 monitoring camera points in several parts of Surabaya City. where each officer oversees 4 areas with 8 CCTVs on the monitoring screen. Although it has had a positive impact on the implementation of ticketing, there are many things that should be evaluated from the process of running E-TLE at Surabaya Police Station. Mainly in the process of implementing and providing maximum fines, as well as the limited number of employees and time in ETLE supervision. So that the Process on Performance and the Facilities used should be evaluated in the running of the ETLE system in Surabaya City. The method used in this research is descriptive qualitative. The focus of this research is to find out the results of the Evaluation of the E-Ticket Policy Program (E-TLE) at the Surabaya City Road Intersection The theory used in the research is Gupta & Jana's Evaluative performance theory. There are 4 indicators from this theory, namely total costs and fines, quality of planning and control, quality of decision making and system characteristics. The data collection technique in this study is by conducting interviews, observation and documentation. In this research, from these 4 indicators, some are quite appropriate, but there are still many shortcomings that should be evaluated from the system and the quality of performance of the Surabaya police litas unit. The performance evaluation of the E-Tilang program in Surabaya shows success in managing total costs and fines, the quality of planning and control, and the quality of decision making. This program includes the use of 40 CCTV camera units and fiber optic networks that support the effectiveness of law enforcement, as well as the management of fair fines. Careful planning and better coordination after the evaluation ensured efficiency in recording violations using gadgets and the E-Tilang application.